Anti-Inflammatory Effects of Antarctic Lichen Umbilicaria antarctica Methanol Extract in Lipopolysaccharide-Stimulated RAW 264.7 Macrophage Cells and Zebrafish Model. (16th February 2021) - Hong, Ju-Mi; Kim, Jung Eun; Min, Seul Ki; Kim, Kyung Hee; Han, Se Jong; Yim, Joung Han; Park, Hyun; Kim, Jin-Hyoung; Kim, Il-Chan
Abstract : Umbilicaria antarctica (UA) is a member of the family Umbilicariaceae. To the best of our knowledge, no studies on its anti-inflammatory effects have been reported yet. In the present study, we examined its ability to suppress inflammatory responses and the molecular mechanisms underlying these abilities using lipopolysaccharide- (LPS-) stimulated RAW 264.7 cells and a zebrafish model of inflammation. We investigated the effects of UA on the production of nitric oxide (NO) and prostaglandin E2 (PGE2 ) in LPS-stimulated RAW 264.7 cells. To explore the anti-inflammatory mechanisms of UA, we measured the mRNA and protein expression of proinflammatory mediators in LPS-stimulated RAW 264.7 cells using quantitative RT-PCR and western blot analyses, respectively. UA significantly inhibited the production of NO, PGE2, interleukin- (IL-) 6, and tumor necrosis factor- (TNF-) α in the LPS-stimulated RAW 264.7 cells. It also suppressed the mRNA and protein expression of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), and nuclear factor- (NF-) κ B activation in LPS-stimulated RAW 264.7 cells and tail pin-cutting-induced zebrafish model. Collectively, these findings indicate that UA significantly inhibits LPS-stimulated inflammatory responses. These effects were considered to be strongly associated with the suppression of NF- κ B activation. Overall, our results demonstrate that UA extract exerts strong anti-inflammatory activities in in vitro and in vivo models and suggest that UA may be an effective novel therapeutic agent for the treatment of inflammatory diseases.